Innovation In The Development Of Black Garlic As An Ingredient In Coffee - Rumaseuw, Ellen Stephanie; Ave Maria, Roma; Saptaningsih, Monica (JURNAL FARMASI GALENIKA, 2024)
The phenomenon of coffee drinking influences thought patterns, health, and behavior in today's society. The joy of coffee comes from its taste and efficacy. Innovation the raw material for coffee in this study is black garlic with ginger powder added. Black garlic is a processed garlic product that contains an organic sulfur compound called S-allylcysteine sulfoxide, which has antioxidant properties. Another benefit of black garlic is that it can increase your body's stamina/vitality. The addition of ginger powder, which acts synergistically as an antioxidant, also contributes to the flavor of the coffee. This is expected to increase the creation of types of coffee-making ingredients that can improve taste and enhance functional benefits for human health. This study aims to determine the correct formulation of black garlic coffee with added ginger powder to have a positive impact on health. Chemical testing is performed by analyzing components such as: Antioxidants and proximate analysis, polyphenols; have potential applications in food and health products, as well as among herbal ingredients that maintain the body's stamina and vitality. The test process of sample analysis is carried out in the laboratory and the data is analyzed descriptively by presenting tables and plots of the obtained results in relation to the product potential. The technology used to develop Black Garlic Coffee is based on the processing of garlic, which is fermented for a period of time at high temperatures to produce new chemical components and recipes. This reserach have results that antioxidant content and detailed analysis of black garlic coffee could make it a globally competitive and local food that boosts stamina and vitality. This is supported by its antioxidant capacity and IC50% content of 8406.0677 ppm, low fat content of 0.20% and carbohydrate content of 37.03%. This is also supported by the moisture content of 53.02%; Ash content 1.53%; Protein 8.23%. One of the antioxidants present in black garlic coffee is total polyphenols, which have been shown containing 0.21% FeCl3 and Folin-Ciocalteu